Relationship Between the Quantity of Nerve Exposure During Bilateral Sagittal Split Osteotomy Surgery and Sensitive Recovery. Issue 5 (July 2017) - Gennaro, Paolo; Giovannoni, Maria Elisa; Pini, Niccolò; Aboh, Ikenna Valentine; Gabriele, Guido; Iannetti, Giorgio; Cascino, Flavia
Abstract : Aim and Objectives: The purpose of this study was to evaluate how different exposures of the V3 nerves during orthognathic surgery impact neurosensory disturbances. Methods: The study included 127 patients who underwent either bilateral sagittal split osteotomy (BSSO) or BSSO with maxillary le Fort 1. They were divided into 6 groups, identified by the quantity of V3 nerve exposure. All patients were examined in a pre-op period and again after 1, 3, 6 months post-op. The standardized tests used were to clarify the objective and subjective neurosensory status of the exposed nerve. Neurosensory evaluation included; a pin prick test, the 2 points discriminator, light touch, warm and cold tests, and blunt discrimination. They were all done bilaterally on the lower lip area. Results: In only 2 patients the nerve was damaged during surgery and thus they were not included in this study. In 10.2% of patients there was no nerve exposure, 25.2% had longitudinal vestibular segment nerve exposed, 22.8% had the longitudinal upper-vestibular segment exposed, 20.5% had the longitudinal lower-vestibular segment exposed, 14.2% had the longitudinal upper-lower-vestibular segment exposed, and in 7.1% of patients the nerve was totally exposed. Given the estimated time of 1 month there was 100% recovery in patients whose nerve was unexposed. Considering the other patients, the authors had a variable number of patients who did not recover completely. Conclusion: The authors estimate a correlation between the recovery time and the quantity of the exposed nerve. There is a high incidence of neurosensory disturbance in the lower lip and chin after BSSO and intraoperative quantity of nerve exposure.